1992
DOI: 10.1002/ar.1092330108
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the morphology of the extratesticular rete and ductuli efferentes in the goat

Abstract: The morphology of the extratesticular rete and ductuli efferentes was reexamined in serial cross sections collected from the entire mass of the efferent ductules and in longitudinal sections collected from the partially unraveled efferent ductules. The extratesticular rete forms a 3-4-mm-long sac-like dilatation, which, within the head of the epididymis, has a wide lumen (up to 4 mm) and gives off along its length numerous evaginations, which, in turn, make connections with the ductuli efferentes. The latter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Although steroid production in the developing fetal gonad is negligible, androstenedione is produced by the fetal adrenal. The androgen and estrogen receptors appear to be expressed in germ cells, Sertoli cells, and precursor peritubular cells in the embryo, such that the fetal gonad may be responsive to endocrine disruptors (19,20). However, potential toxicology of these environmental compounds also needs to be considered.…”
mentioning
confidence: 97%
“…Although steroid production in the developing fetal gonad is negligible, androstenedione is produced by the fetal adrenal. The androgen and estrogen receptors appear to be expressed in germ cells, Sertoli cells, and precursor peritubular cells in the embryo, such that the fetal gonad may be responsive to endocrine disruptors (19,20). However, potential toxicology of these environmental compounds also needs to be considered.…”
mentioning
confidence: 97%
“…This possibility was confirmed at the electron microscopic level by Hamilton (1972) 17) . Later, the presence of lymphocytes penetrating into the epithelial layers of TR was found at the electron microscopic level in some animal species except for mice 7,9,10) . In the present study, we first found similar lymphocytes in normal mice.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, previous studies have demonstrated that quite a few lymphocytes occasionally penetrate into the RT in the normal rat, cat, goat, boar, and bull [6][7][8][9][10][11] . Moreover, the presence of penetrating lymphocytes inside the TR in the normal state has been reported in the monkey 6) .…”
Section: Introductionmentioning
confidence: 99%
“…There are three non-ciliated cell types in man (Morita 1966), bull (Goyal and Hrudka 1981), goat (Gray et al 1983;Goyal et al 1992) and, at least, four in the dog (Hess and Bassily 1988). In man, bull and goat, unlike in the rat, the type I cell contains no granules or vacuoles, the type II cell contains numerous dense granules, while the type III cell exhibits no granules, but contains numerous vacuoles (Morita 1966;Goyal and Hrudka 1981;Goyal et al 1992). In birds, two types of non-ciliated cells, present, respectively, in the proximal and distal segments of the efferent duct, have been reported (Budras and Sauer 1975;Aire and Malmquist 1979;Aire 1979).…”
Section: Discussionmentioning
confidence: 97%